The Impact of Digital Transformation on Sustainable Business of Commercial Banks in an Emerging Economy - Nguyen, Minh Tri; Truong, Thanh Vo Phuc; Tan, Hiep Ngo; Dang, Thanh Vu; Ngoc, Tran Thi Bich (International Review of Management and Marketing, 2025)
This study aims to clarify the mediating roles of three factors—corporate governance, perceived efficiency, and financial performance—in the relationship between digital transformation and sustainable business practices among Joint Stock Commercial Banks (JSCBs) in Vietnam. Data were collected from 270 customers with experience using services at JSCBs and analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS-SEM) technique. The results indicate that corporate governance and financial performance play statistically significant mediating roles in the relationship between digital transformation and sustainable business. Conversely, no empirical evidence was found to support the mediating role of perceived efficiency in this relationship. These findings not only contribute empirical insights to the literature on digital transformation and sustainability in the banking sector but also offer practical managerial implications for JSCBs in designing digitalization strategies and enhancing competitiveness in an increasingly digital landscape.